Heimweh; The siren; The loaded gun; Liebereich; "Iupiter Tonans;" "Sis;" Thor's emerald; Guile - Long, John Luther, 1861-1927; Adams, John Wolcott, 1874-1925; Gibbs, George, 1870-1942; Jacobs, W. L. (William Leroy), 1869-1917; Stephens, Alice Barber, 1858-1932; Strothmann, F. (Frederick), 1872-1958 (Salt Lake City, UT : Project Gutenberg, 2024)
"Heimweh; The siren; The loaded gun; Liebereich; 'Iupiter Tonans;' 'Sis;' Thor's..." by John Luther Long is a collection of short stories written in the early 20th century. The text begins with a poignant exploration of human relationships, love, and the passage of time, focusing especially on themes of happiness and loss. Notably, one of the stories introduces us to Betsy and John, a couple who, despite a modest existence, find joy in their simple lives and unconditional love for each other. The opening of the book sets the stage for an emotionally rich narrative, beginning with the lives of John and Betsy as they navigate their humble beginnings together. They are portrayed as a young couple in love, content with their lack of material wealth and focused on their family. As the story progresses, it delves into the challenges and heartaches they face, particularly during the Civil War, when John's sons go off to fight, leaving Betsy to grapple with the fear of losing her loved ones. Their tale is woven with moments of light-heartedness and profound sorrow, suggesting a narrative that intertwines joyous memories with the sorrow of inevitable loss, laying a foundational emotional landscape for the rest of the collection. (This is an automatically generated summary.)
Release date is 2024-12-19
Richard Tonsing, Charlene Taylor, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Short stories, American; American fiction -- 20th century